PENERAPAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MITRA KERJA TERBAIK CADDY PADA PT. PONDOK INDAH PADANG GOLF MENGGUNAKAN METODE TOPSIS - Ika Komala; Atang Susila (CV. Multi Kreasi Media, 2024)
Information System is an integration of information technology used in a group or organization in assisting the operation of the environment, information systems are very influential in organizational achievement because information systems have the advantage of continuing to berkembang.PT. Pondok Indah Padang Golf is a company engaged in sports. located precisely on Jl. Metro Pondok Indah, South Jakarta. This international standard field with a beautiful grass bed and attractive facilities in it. The process of selecting the best partners in PT. PONDOK INDAH GOLF COURSE is still not well realized because there is no supportive system for the selection of the best working partners. Currently, the selection process is only based on the assessment of attendance, number of work and has not used the right calculation method to determine the best work partner, thus causing social jealousy in every election result given. With the creation of this decision support system, it is hoped that it can help in making a decision more quickly, precisely and accurately in accordance with the desired assessment criteria fairly. In this study, a decision support system application will be designed using the TOPSIS method. Based on the description of the problem above, the author will design a study with the title